2012
DOI: 10.1093/molehr/gas008
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve status in young women is associated with altered gene expression in membrana granulosa cells

Abstract: Diminished ovarian reserve (DOR) is a challenging diagnosis of infertility, as there are currently no tests to predict who may become affected with this condition, or at what age. We designed the present study to compare the gene expression profile of membrana granulosa cells from young women affected with DOR with those from egg donors of similar age and to determine if distinct genetic patterns could be identified to provide insight into the etiology of DOR. Young women with DOR were identified based on FSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 51 publications
(51 reference statements)
1
39
1
4
Order By: Relevance
“…That premature luteinization negatively impacts oocyte quality, fertilization and implantation is supported by Skiadas et al (2012) who demonstrated an association between low functional ovarian reserve in older women and premature luteinization, clinically characterized by higher peripheral LH and lower AMH levels. Also, oocyte numbers and top quality embryo numbers have been reported to be significantly higher in normal patients than in women with premature luteinization (Bosch et al 2003, Elnashar 2010).…”
Section: Discussionmentioning
confidence: 92%
“…That premature luteinization negatively impacts oocyte quality, fertilization and implantation is supported by Skiadas et al (2012) who demonstrated an association between low functional ovarian reserve in older women and premature luteinization, clinically characterized by higher peripheral LH and lower AMH levels. Also, oocyte numbers and top quality embryo numbers have been reported to be significantly higher in normal patients than in women with premature luteinization (Bosch et al 2003, Elnashar 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Although infertility treatments have been improved through assisted reproductive technology (ART) over the past 30 years, the molecular reasons of infertility have not been fully identified [31]. Women who respond well to fertility treatments are defined as having normal ovarian reserve (NOR).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors are important in ovarian steroidogenesis, luteinization, and therefore, progesterone synthesis and fertility. Skiadas et al [42] found a 2.19-fold increased expression of the LHCGR gene in DOR patients over NOR patients. The increased gene expression of LHCGR in DOR patients could be explained by premature luteinization and upregulation of luteinizing hormone receptors on follicular cells, which might occur with DOR patients given the increased FSH in the follicular phase.…”
Section: Luteinizing Hormone/choriogonadotropin Receptor (Lhcgr)mentioning
confidence: 97%
“…Typically, serum AMH values below 0.8 ng/mL have been found to be consistent with elevated FSH levels and severely diminished ovarian reserve [6]. Skiadas et al [42] examined membrana granulosa cells from women with DOR.…”
Section: Anti-müllerian Hormone (Amh)mentioning
confidence: 99%